Pengurangan Waktu Proses Intra Transportasi Menggunakan Value Stream Mapping - Jeffery Tipawael; I Gede Agus Widyadana (Jurnal Titra, 2016)
Abstract: PT Y is one of the companies in Surabaya engaged in manufacturing cigarattes. PT Y want to identify the waste so that it can be improved continuously. PT Y believed that the process has the potential to improve intra transportation process. Identification of waste to the process intra transportation especially performed on process delivery of PPIC TAC and PMD. The method used to identify the waste is value stream mapping. Value stream mapping that aimed to describe the process as a whole and reduce the lead time of a process. Waste that was found in the process of intra transportation is waiting, transportation and overprocessing. Proposals made reduce the lead time of each process. Lead time delivery of tobacco and clove from PPIC TAC to PMD successfully reduce by 2.56%. Lead time delivery of sliced tobacco from PMD to SKM successfully reduced by 46.73%. Lead time delivery of sliced tobacco from PMD to SKT successfully reduced by 2.59%.